Tumour-educated circulating monocytes are powerful candidate biomarkers for diagnosis and disease follow-up of colorectal cancer - Hamm, Alexander; Prenen, Hans; Delm, Wouter Van; Matteo, Mario Di; Wenes, Mathias; Delamarre, Estelle; Schmidt, Thomas; Weitz, Jürgen; Sarmiento, Roberta; Dezi, Angelo; Gasparini, Giampietro; Rothé, Françoise; et al. (Gut, 2016)
Objective Cancer immunology is a growing field of research whose aim is to develop innovative therapies and diagnostic tests. Starting from the hypothesis that immune cells promptly respond to harmful stimuli, we used peripheral blood monocytes in order to characterise a distinct gene expression profile and to evaluate its potential as a candidate diagnostic biomarker in patients with colorectal cancer (CRC), a still unmet clinical need. - Design We performed a case-control study including 360 peripheral blood monocyte samples from four European oncological centres and defined a gene expression profile specific to CRC. The robustness of the genetic profile and disease specificity were assessed in an independent setting. - Results This screen returned 43 putative diagnostic markers, which we refined and validated in the confirmative multicentric analysis to 23 genes with outstanding diagnostic accuracy (area under the curve (AUC)=0.99 (0.99 to 1.00), Se=100.0% (100.0% to 100.0%), Sp=92.9% (78.6% to 100.0%) in multiple-gene receiver operating characteristic analysis). The diagnostic accuracy was robustly maintained in prospectively collected independent samples (AUC=0.95 (0.85 to 1.00), Se=92.6% (81.5% to 100.0%), Sp=92.3% (76.9% to 100.0%). This monocyte signature was expressed at early disease onset, remained robust over the course of disease progression, and was specific for the monocytic fraction of mononuclear cells. The gene modulation was induced specifically by soluble factors derived from transformed colon epithelium in comparison to normal colon or other cancer histotypes. Moreover, expression changes were plastic and reversible, as they were abrogated upon withdrawal of these tumour-released factors. Consistently, the modified set of genes reverted to normal expression upon curative treatment and was specific for CRC. - Conclusions Our study is the first to demonstrate monocyte plasticity in response to tumour-released soluble factors. The identified distinct signature in tumour-educated monocytes might be used as a candidate biomarker in CRC diagnosis and harbours the potential for disease follow-up and therapeutic monitoring.